Kesulitan Keuangan Perusahaan Semasa Covid-19 - Galant Emerald; Zaitul Zaitul; Listiana Sri Mulatsih (Owner : Riset dan Jurnal Akuntansi, 2023)
Corporate financial distress is a hot topic among practitioners and academics. This financial difficulty can lead to a bankrupt position if not handled properly. Much research has been done on financial problems, but it was still limited during the Covid-19 pandemic. Some companies affected by could-19 (lockdown policy) may experience finances such as tourism, transportation and other sectors. This research investigates whether there are differences in financial difficulties before and during the pandemic (2018-2019 and 2020-2021). In addition, this study also aims to test whether financial ratios contribute to financial distress. The role of audit committee effectiveness as a moderating variable between financial ratios and financial distress is also tested in this study. Using 18 companies engaged in the restaurant, hotel and tourism sector as research samples (41.42% of the population) with the data period 2018-2021. Different tests and regression tests were used to answer research questions. The results show that the sample companies experienced financial difficulties during the pandemic (2020-2021) because their z-score values were lower than 2018-2019, with significant differences. The regression results show that liquidity has a positive effect on financial distress. The audit committee's effectiveness acts as a moderating variable between leverage and financial difficulties. In other words, a high level of audit committee effectiveness will strengthen the positive leverage relationship with the z-score or lower financial distress. One of the control variables (firm age) has a negative effect on the z-score. In other words, the older the company, the lower the level of financial distress. This research has theoretical implications where agency theory can explain the relationship between leverage and financial condition with the role of audit committee effectiveness.